Toxic Palestine : the Ohio train incident [videorecording (DVD)] - Simone, Jonathan; Sampson, Carl (Director); B., James ([WowNow Entertainment], 2023)
Investigating one of the worst ecological disasters in US history. Investigates the incident that caught the headlines of February 3, 2023, when 38 cars of a Norfolk Southern freight train carrying hazardous materials derailed in East Palestine, Ohio, causing several railcars to burn for more than two days. When emergency crews conducted a controlled burn of several railcars at the request of state officials, they released hydrogen chloride and phosgene into the air. Although officials reported that air quality readings were not showing anything concerning, residents reported a suspicious chemical smell in their area.